Emergence of a novel lineage containing a prophage in emm/M3 group A Streptococcus associated with upsurge in invasive disease in the UK. Issue 6 (24th June 2016) - Al-Shahib, Ali; Underwood, Anthony; Afshar, Baharak; Turner, Claire E.; Lamagni, Theresa; Sriskandan, Shiranee; Efstratiou, Androulla
Abstract : A sudden increase in invasive Group A Streptococcus (iGAS) infections associated with emm /M3 isolates during the winter of 2008/09 prompted the initiation of enhanced surveillance in England. In order to characterise the population of emm /M3 GAS within the UK and determine bacterial factors that might be responsible for this upsurge, 442 emm /M3 isolates from cases of invasive and non-invasive infections during the period 2001–2013 were subjected to whole genome sequencing. MLST analysis differentiated emm /M3 isolates into three sequence types (STs): ST15, ST315 and ST406. Analysis of the whole genome SNP-based phylogeny showed that the majority of isolates from the 2008–2009 upsurge period belonged to a distinct lineage characterized by the presence of a prophage carrying the speC exotoxin and spd1 DNAase genes but loss of two other prophages considered typical of the emm /M3 lineage. This lineage was significantly associated with the upsurge in iGAS cases and we postulate that the upsurge could be attributed in part to expansion of this novel prophage-containing lineage within the population. The study underlines the importance of prompt genomic analysis of changes in the GAS population, providing an advanced public health warning system for newly emergent, pathogenic strains.